The Essence of Christianity in Romans 12:1-2 - Karwur, Edwin J.G. (STT INDONESIA MANADO, 2021)
Christianity is completely being a work of God, that should be displayed by the Christians holistically. The probles is, Christianity is being parralled with all existed world’s religions. In addition to it, within the Christian communities, the meaning of the Christian faith is oftenly disassociated with the praxis of Christianity. This article was designed to exegete Romans 12:1-2 in order to find out the real essence of Christianity. By using the descriptive explanation methodology, this article proved that the essence of Christianity was completely distincted to the meaning of the world’s religions. In addition to it, Christianity does not recognize the notion that disassociates between faith and its implementation. The historical and literaly contexts of the letter confirmed that Romans 12:1-2 functions as an inferential that connects with the previous chapters and extends to next chapters. Chapters 1-11 indicatively, indicates that Christianity was begun, being kept and will be completed by the grace of God through the faith in Jesus Christ. Chapters 12-15, imperatively exhorts the Christians to live out their faith by holistically present their lives as a living sacrifice to God through their ethics of love.